Mitigation of Insert Separator Damage in Open-End Machines - Filly Pravitasari; AFRIANI KUSUMADEWI; Feny Nurherawati (Universitas Insan Cendekia Mandiri, 2023)
Insert separators are part of the Open-end spinning machine that plays an important role in the process of feeding the fiber to the rotor. The function of the insert separators is as a conductor of drawing sliver which has been combed into individual fibers by adjusting the angle point of the insert separators. Damage to insert separators affects the number of slub yarns in the process of making Open-end spinning yarn. Consumption of using the separator insert continuously can make damage (eroded). The damage occurred during 20 days (four weeks) of 35.25 times of observation. The number of damaged separator inserts requires a repair whether the repair is done by patching, but in fact repair by patching is not an effective way, because the age of the patch only lasts approximately 1 week. Therefore, patch repair is not carried out, the best effort is to replace the separator insert.